Effective regulations of FinTech innovations: the case of China - Bu, Ya; Li, Hui; Wu, Xiaoqing (Economics of innovation and new technology, 2022)
In recent years, China has witnessed the rapid development of FinTech and become a leading country in the world. However, the regulatory mode under the traditional regulatory framework in China is difficult to effectively deal with the potential risks of FinTech innovations, which leads to frequent risk events. Firstly, based on the in-depth analysis of some research reports and regulatory policies, we clearly define the development status and essential characteristics of FinTech companies and regulatory authorities. Secondly, we construct a two-player evolutionary game model to depict the evolutionary game behavior between FinTech companies and regulatory authorities and analyze influencing factors of their strategic choices. We find that strategic choices of FinTech companies are mainly affected by extra benefits from non-compliance innovation, rewards from compliance innovation and penalty intensity from regulatory authorities, and strategic choices of regulatory authorities are mainly affected by regulatory costs, social evaluation and negative externalities. Finally, based on the realities of excessive innovations and insufficient regulations in China's FinTech industry, we put forward some policy suggestions to promote the effective regulations of FinTech innovations and achieve a balance between regulation and innovation.